H. R. H. - Steel, Danielle (London : Corgi Books, 2007)
After four years of college in America, Princess Christianna is determined not to return to the stiff, formal lifestyle of her father's court and, hoping to make a difference in the world, persuades her father to allow her to volunteer for the Red Cross in East Africa.
Keywords: Princesses -- Fiction; Love stories